2020
DOI: 10.1155/2020/2514090
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of FEN1 Is Associated with the Tumor Progression and Prognosis of Hepatocellular Carcinoma

Abstract: Background. Studies show that patients with hepatocellular carcinoma (HCC) have poor prognosis, particularly when patients are diagnosed at late stages of the disease development. The flap endonuclease 1 (FEN1) gene is overexpressed in multiple malignant tumors and may promote tumor aggressiveness. However, its expression profile and functional roles in HCC are still unclear. Here, we evaluated the molecular mechanisms of FEN1 in HCC. Methods. The expression of FEN1 in HCC was evaluated using HCC mRNA expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…So far, knowledge on the utilization of the structure-specific endonuclease FEN1 during viral infections is limited. Only recently FEN1 was recognized as a key enzyme for hepatitis B virus cccDNA formation and as a marker for hepatitis B virus-associated hepatocellular carcinoma [45][46][47][48][49]. This emphasizes that blocking enzymatic activities of DNA repair proteins such as FEN1 may represent novel therapeutic opportunities for the treatment of viral diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…So far, knowledge on the utilization of the structure-specific endonuclease FEN1 during viral infections is limited. Only recently FEN1 was recognized as a key enzyme for hepatitis B virus cccDNA formation and as a marker for hepatitis B virus-associated hepatocellular carcinoma [45][46][47][48][49]. This emphasizes that blocking enzymatic activities of DNA repair proteins such as FEN1 may represent novel therapeutic opportunities for the treatment of viral diseases [50].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zhang et al demonstrated that in hepatocellular carcinoma, FEN1 expression was positively correlated with cell cycle and DNA replication pathway-related genes such as c-Myc, survivin, and cyclin D1, silencing FEN1 could inhibit cell proliferation and migration by regulating expression of these genes. 29 Becker et al reported that flap endonuclease overexpression was a driver of genome instability in yeast and human cells that impairs DNA replication in a manner dependent on its interaction with PCNA. 22 Wang et al demonstrated that the FEN1 protein level was tightly controlled by sequential phosphorylation, SUMOylation, and ubiquitination in a cell cycle-dependent manner in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs and endonuclease ( 15 ) are involved in the pathogenesis of liver cancer. Most lncRNAs promote the proliferation of HCC through microRNAs ( 16 ).…”
Section: Discussionmentioning
confidence: 99%